Successful BRAF/MEK inhibition in a patient with BRAFV600E-mutated extrapancreatic acinar cell carcinoma - Busch, Elena; Kreutzfeldt, Simon; Agaimy, Abbas; Mechtersheimer, Gunhild; Horak, Peter; Brors, Benedikt; Hutter, Barbara; Fröhlich, Martina; Uhrig, Sebastian; Mayer, Philipp; Schröck, Evelin; Stenzinger, Albrecht; et al. (Cold Spring Harbor molecular case studies, 2020)
Pancreatic acinar cell carcinoma (PAC) is a rare disease with a poor prognosis. Treatment options for metastatic PAC are limited and often follow chemotherapeutic regimens for pancreatic ductal adenocarcinoma. Although recurrent genomic alterations, such as BRAF fusions and defects in genes involved in homologous recombination DNA repair, have been described in PAC, data on the clinical efficacy of molecularly guided, targeted treatment are scarce. Here we describe the case of a 27-yr-old patient with BRAFV600E-mutated PAC who was successfully treated with a combination of BRAF and MEK inhibitors. The patient presented to our clinic with abdominal pain and weight loss. Imaging showed extensive retroperitoneal disease as well as mediastinal lymphadenopathy. Because of elevated α-fetoprotein (AFP) levels and inconclusive histologic findings, a germ cell tumor was suspected; however, PEI chemotherapy was unsuccessful. A repeat biopsy yielded the diagnosis of PAC and treatment with FOLFIRINOX was initiated. Comprehensive molecular profiling within the MASTER (Molecularly Aided Stratification for Tumor Eradication Research) precision oncology program revealed a somatic BRAFV600E mutation and a germline PALB2 stop-gain mutation. Therapy was therefore switched to BRAF/MEK inhibition, resulting in almost complete remission and disease control for 12 mo and a remarkable improvement in the patient's general condition. These results indicate that BRAF alterations are a valid therapeutic target in PAC that should be routinely assessed in this patient population.
Im Titel ist der Ausdruck "V600E" hochgestellt
Gesehen am 25.05.2023